Pd-Gated N-Polar GaN/AlGaN High-Electron-Mobility Transistor for High-Sensitivity Hydrogen Gas Detection - Long Ge; Haineng Bai; Yidi Teng; Xifeng Yang (Crystals)
Hydrogen gas sensing is critical for energy storage, industrial safety, and environmental monitoring. However, traditional sensors still face challenges in selectivity, sensitivity, and stability. This work introduces an innovative N-polar GaN/AlGaN high-electron-mobility transistor (HEMT) with a 10 nm Pd catalytic layer as a hydrogen sensor. The device achieves ppm-level H2 detection with rapid recovery and reusability, which is comparable to or even exceeds the performance of conventional Ga-polar HEMTs. The N-polar structure enhances sensitivity through its unique polarization-induced 2DEG and intrinsic back barrier, while the Pd layer catalyzes H2 dissociation, forming a dipole layer that can modulate the Schottky barrier height. Experimental results demonstrate superior performance at both room temperature and elevated temperatures. Specifically, at 200 °C, the sensor exhibits a response of 102% toward 200 ppm H2, with response/recovery times of 150 s/17 s. This represents a 96% enhancement in sensitivity and a reduction of 180 s/14 s in response/recovery times compared to room-temperature conditions (23 °C). These findings highlight the potential of N-polar HEMTs for high-performance hydrogen sensing applications.